2018
DOI: 10.3390/ma12010076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ce Addition on Modifying the Microstructure and Achieving a High Elongation with a Relatively High Strength of As-Extruded AZ80 Magnesium Alloy

Abstract: Forming magnesium alloys with rare earth elements (La, Gd, Nd, Y, Ce) is a routine method for modifying their microstructure and properties. In the present work, the effect of Ce addition on the microstructure evolution and the mechanical properties of as-extruded Mg-8Al-0.5Zn (AZ80) alloy was investigated. All of the extruded AZ80-xCe (x = 0, 0.2, 0.8 and 1.4 wt %) alloys exhibited equiaxed grains formed by fully dynamic recrystallization, and the grain size of the extruded AZ80 alloy was remarkably reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…According to previous experience in our laboratory, the cylindrical ingots were homogenized at 415 °C for 20 h and then quenched in cold water immediately. [ 12,13 ] The forging of the materials was conducted in a 200‐ton hydraulic press (TDY33‐200A, Tianjin Forging Machine Tool Factory, China). To study the effect of the forging process parameters on the as‐forged AZ80 alloy, forging of the AZ80 alloy was carried out for the same forging reduction (27.5%) at five different forging temperatures (250, 300, 350, 400, and 450 °C) as well as at the same temperature (400 °C) and for four different forging reductions (7.5%, 17.5%, 27.5%, and 37.5%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous experience in our laboratory, the cylindrical ingots were homogenized at 415 °C for 20 h and then quenched in cold water immediately. [ 12,13 ] The forging of the materials was conducted in a 200‐ton hydraulic press (TDY33‐200A, Tianjin Forging Machine Tool Factory, China). To study the effect of the forging process parameters on the as‐forged AZ80 alloy, forging of the AZ80 alloy was carried out for the same forging reduction (27.5%) at five different forging temperatures (250, 300, 350, 400, and 450 °C) as well as at the same temperature (400 °C) and for four different forging reductions (7.5%, 17.5%, 27.5%, and 37.5%).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work, the influence of Ce addition on an as‐extruded AZ80 alloy was investigated, and it was found that the addition of Ce had a remarkable grain refinement effect and significantly promoted the deformability of extruded AZ80 alloys. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ce addition could also promote the formation of new precipitates in the studied alloy, increasing the total fraction of the precipitates. Apart from the direct effect of these precipitates on the hardness and strengths, they would have a pinning effect on the grain boundaries, causing further refinement [31,32]. The decrease in the elongation (Table 2) could be due to the larger volume fraction of precipitates formed in the ZK60-3Ce alloy.…”
Section: Microstructural Observationmentioning
confidence: 99%
“…The bulk-shaped phases marked with point f in the grains are Al 8 Mn 5 , which has too low a content in the matrix to be defined in the XRD pattern, while it can be defined in EDS. Another important phase is Al 4 Ce (point g), with the shape of a short rod or needle, whose formation is due to the addition of Ce [25]. Figure 6 depicts the microstructure evolution with the deformation of extrusion and four-pass extension at 240 • C. It can be seen that the grain size achieves great refinement from the backward extrusion to the fourth extension, whose grain size is 5.2 µm.…”
Section: Microstructure Evolutionmentioning
confidence: 99%